Dynamics conflict and cooperation for group stability among selected government-assisted cooperatives in Region IV, Philippines. - Visco, E. S. (2003)
The research was conducted to study the management dynamics of selected government-assisted cooperatives in Region I in terms of conflict and cooperation among their members. Specifically, it aimed to 1. determine and analyze the nature of conflict and cooperation among members of the cooperatives under study; 2. determine the factors that influence conflict and cooperation; 3. identify the consequences of conflict and cooperation on the stability the cooperatives under study; and 4. formulate recommendations to help sustain the stability of government-assisted cooperatives in other parts of the country as well. The respondents' internal factors (socio-demographic characteristics, socio-psychological characteristics and group factors) and external actors (perception towards extension professionals and researchers, towards their leaders and institutional support/incentives) were assumed to affect their level of conflict and cooperation in their respective cooperative. Results showed that there were significant relationships between the respondents group actors like group relation, group processes, and coordination with other members of the cooperative and their level of conflict and cooperation in the cooperative's activities. Similarly, socio-psychological characteristics like interpersonal orientation affect their level of conflict with their cooperative leaders. Almost all statements determining the respondents' interpersonal characteristics got an "agree" stand for positive and "disagree" for negative statements. Most of the respondents did not have conflict with their leaders. This finding was confirmed in their perception towards their leaders. There was a significant relationship between the respondents' perception towards their leaders and their level of cooperation in their cooperative activities. The respondents' high perceptions towards their leaders enable the respondents to believe that there was a "high" level of cooperation among members. In turn, the level of cooperation among members affects the stability of the cooperatives under study.
Keywords: Cooperatives; Government-funded programs